Repeated percutaneous cryoablation and radiofrequency ablation for renal tumors in a solitary kidney: report of two cases - Ulys, Albertas; Čerškutė, Minija; Naruševičiūtė, Ieva; Trakymas, Mantas; Kulboka, Arūnas (Lietuvos chirurgija, 2016)
IntroductionPercutaneous cryoablation and radiofrequency ablation are options of minimally invasive treatment while maximizing nephron preservation. It is increasingly used in patients with comorbid conditions, multiple renal cell carcinomas, for patients with a single kidney and/or inherited renal cancer syndromes especially in situations when there is a need to preserve renal function. The aim of this presentation is to show the benefits (effectiveness and safety) of cryoablation for the patients with a solitary kidney from our experience. Case reportsWe present 2 cases of the patients with a solitary kidney and solid renal masses of
Keywords: minimally invasive therapies; renal tumors; interventional radiology